Cytokines and HIF-1α as dysregulation factors of migration and differentiation of monocyte progenitor cells of endotheliocytes in the pathogenesis of ischemic cardiomyopathy - O. A. Denisenko; S. P. Chumakova; O. I. Urazova; V. M. Shipulin; A. S. Pryakhin (Acta Biomedica Scientifica, 2022)
Background. Angiogenic endothelial dysfunction and progenitor endothelial cells (EPCs) in ischemic cardiomyopathy (ICMP) have not been studied enough.The aim. To establish the nature of changes in the cytokine profile and HIF-1α in blood and bone marrow associated with impaired differentiation of monocytic progenitor cells of endotheliocytes (CD14+VEGFR2+) in the bone marrow and their migration into the blood in patients with coronary heart disease (CHD), suffering and not suffering from ICMP.Materials and methods. A single-stage, single-centre, observational case-control study was conducted involving 74 patients with CHD, suffering and not suffering from ICMP (30 and 44 people, respectively), and 25 healthy donors. In patients with CHD, bone marrow was obtained during coronary bypass surgery, peripheral blood – before surgery. Healthy donors were taken peripheral blood. The number of CD14+VEGFR2+ in bone marrow and blood was determined by flow cytometry; the concentration of IL-6, TNF-α, M-CSF, GM-CSF, MCP-1 and HIF-1α – by the method of enzyme immunoassay.Results. A high content of CD14+VEGFR2+ cells in the blood of patients with CHD without cardiomyopathy was established relative to patients with ICMP against the background of a comparable number of these cells in myeloid tissue. Regardless of the presence of ICMP in the blood, patients with CHD showed an excess of TNF-α, a normal concentration of IL-6, GM-CSF, HIF-1α and a deficiency of M-CSF, and in the bone marrow supernatant, the concentration of IL-6 and TNF-α exceeded that in the blood plasma (the level of GM-CSF – only in patients without cardiomyopathy). With ICMP, the normal concentration of MCP-1 was determined in the blood plasma, and with CHD without cardiomyopathy, its elevated content was determined.Conclusion. The formation of ICMP is accompanied by insufficient activation of EPCs migration with the CD14+VEGFR2+ phenotype in blood without disruption of their differentiation in the bone marrow, which associated with the absence of an increase in the concentration of MCP-1 in blood plasma and not associated with the plasma content of M-CSF, GM-CSF, HIF-1α, IL-6 and TNF-α.